1987
DOI: 10.1104/pp.84.2.225
|View full text |Cite
|
Sign up to set email alerts
|

Catalase Degradation in Sunflower Cotyledons during Peroxisome Transition from Glyoxysomal to Leaf Peroxisomal Function

Abstract: First order rate constants for the degradation (degradation constants) of catalase in the cotyledons of sunflower (Helianthus annums L.) were determined by measuring the loss ofcatalase containing "C-labeled heme. During greening of the cotyledons, a period when peroxisomes change from glyoxysomal to leaf peroxisomal function, the degradation of glyoxysomal catalase is sigificantly (P =

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
(39 reference statements)
3
18
0
Order By: Relevance
“…The results on the synthesis of catalase presented here supplement the data from previous studies on the degradation of catalase (5). Now, all data for a quantitative description of catalase turnover in sunflower cotyledons are available, i.e.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The results on the synthesis of catalase presented here supplement the data from previous studies on the degradation of catalase (5). Now, all data for a quantitative description of catalase turnover in sunflower cotyledons are available, i.e.…”
Section: Discussionsupporting
confidence: 70%
“…Thereafter it rapidly decreased and remained almost constant The results on catalase synthesis and degradation (5) showed that light had a dual effect on catalase turnover during the formation of the leaf peroxisome population in stage II. On one hand catalase degradation was delayed, whereas on the other hand light was the stimulus which maintained catalase synthesis at a higher level than in the dark.…”
Section: Time Course Of Catalase Activity and Catalase Hematinmentioning
confidence: 99%
See 1 more Smart Citation
“…Refs. 4,6, and this paper) the mechanism of regulation has not been determined but could be the result of changes in rates of synthesis, degradation, or by covalent modification of the protein. The determination by Eising et al (3) that the sharp decline in catalase activity in greening sunflower cotyledons was due to the formation of an inactive but largely intact protein molecule may be pertinent to studies of environmentally related changes in catalase activity.…”
mentioning
confidence: 99%
“…Results obtained from a few studies indicate that the general mechanism is one of individual protein degradation rather than a degradation of the whole organelles (1, 8,9,11,12,22,27,28). The concept of individual protein degradation suggests that (at least) initiating steps of the degradative pathway are localized in the peroxisomes.…”
mentioning
confidence: 99%